Effect of transcutaneous electrical nerve stimulation (TENS) for the management of postoperative surgical pain after lower extremity amputation: a pilot study - Djurovic, Aleksandar; Ilic, Dejan; Brdareski, Zorica; Plavsic, Aleksandra; Djurdjevic, Slavisa; Lukovic, Gordana (Acta Fisiátrica, 2007)
Transcutaneous electrical nerve stimulation (TENS) is a noninvasive, nonmedical modality.  Objective: To establish the role of TENS for the management of postoperative surgical pain after lower limb amputations. Methods: Randomized controlled trial, which included forty-six subjects who had undergone lower limb amputations, randomly divided into control and treatment group. The control group received standard postoperative care, whereas the treatment group received standard postoperative care plus TENS. Forty subjects successfully completed the study according to the study protocol. The majority of the individuals had undergone transtibial amputation due to complication of diabetes. Five TENS XL-A1 portable devices with four self-adhesive electrodes were used. This was the conventional TENS mode, characterized by the delivery of electrical impulses with a duration of 200 microseconds, frequency of 110 Hz, and amplitude of 44V. Treatment was carried out for 2 hours a day, during 10 days. The evaluation of TENS efficacy was performed using the horizontal VAS (0-100 mm). Student T test was used in the statistical analysis. Results: Pain intensity was significantly diminished in both groups at the tenth in comparison with the first postoperative day. Conclusion: Conventional TENS (dose: 200 microseconds, 110 Hz, 44V), administered two hours a day during ten days, significantly reduced postoperative surgical pain in twenty subjects who had undergone lower limb amputations.